Neonatal Citrobacter koseri Meningitis: Report of Four Cases - Joana Rodrigues; Dalila Rocha; Fátima Santos; Anabela João (Hindawi Limited, 2014)
Citrobacter koseri is a rare cause of neonatal meningitis with predisposal for brain abscesses, and therefore responsible for high mortality and serious neurologic sequelae in this age group. We present the evolution and outcome of four cases of C. koseri meningitis. One of them developed brain abscesses and another one died. The cases show the bacteria's propensity for serious brain damage, despite early and adequate treatment, and the high risk of long-term neurologic complications in survivors, which imposes a close follow-up.